2012
DOI: 10.1161/circinterventions.112.968347
|View full text |Cite
|
Sign up to set email alerts
|

Flow Patterns at Stented Coronary Bifurcations

Abstract: Background— The ideal bifurcation stenting technique is not established, and data on the hemodynamic characteristics at stented bifurcations are limited. Methods and Results— We used computational fluid dynamics analysis to assess hemodynamic parameters known affect the risk of restenosis and thrombosis at coronary bifurcations after the use of various single- and double-stenting techniques. We assessed the distributions and surface integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 36 publications
1
48
1
2
Order By: Relevance
“…This indicates that the stent implantation has reduced the wall shear stresses. In a previous study a stented coronary artery was analyzed and the maximum stress observed at the stented region is recorded to be greater than 2.3 Pa [33]. But, the present study exhibited a maximum shear stress of 12 Pa in the bifurcated stented region of femoral artery.…”
Section: Blood Pressure Stagescontrasting
confidence: 62%
See 1 more Smart Citation
“…This indicates that the stent implantation has reduced the wall shear stresses. In a previous study a stented coronary artery was analyzed and the maximum stress observed at the stented region is recorded to be greater than 2.3 Pa [33]. But, the present study exhibited a maximum shear stress of 12 Pa in the bifurcated stented region of femoral artery.…”
Section: Blood Pressure Stagescontrasting
confidence: 62%
“…Blood is usually a non-Newtonian fluid flowing through the artery. However, blood behaves as Newtonian fluid at high strain rate [28][29][30][31][32][33][34][35][36] and the density of blood is assumed 1050 kg/m 3 . The cell zone inside the artery is selected as blood and a steady state blood flow is assumed in the analysis.…”
Section: Computational Analysismentioning
confidence: 99%
“…Measurements of bifurcation angle in this study are in line with the average bifurcation angle reported by these studies, with diseased LAD having left coronary angulation of more than 80° (mean angle: 94.3°), while the normal LAD having angulation of less than 80° (mean angle: 76.5°). This strong relationship between the angle of the left coronary artery and the presence of plaques within the left coronary bifurcation could be used as guidance for analysis of potential effects of the hemodynamics on the local characteristics and distribution of plaques [2429], although further studies are warranted to evaluate the potential value of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,20,24,39,40 Similarly, computational fluid dynamics (CFD) simulations have been widely used to investigate the hemodynamic properties of stented arteries and their implications for neointimal hyperplasia. 3,4,15,18,23,33 However, the only numerical studies conducted on stent mis-sizing were found to be on balloon-expandable stents deployed in straight cylindrical models of healthy 3,18 or calcified coronary arteries. 37 Due to the significant differences in their deployment procedures, the results from these studies could not be adopted for self-expandable Nitinol stents.…”
Section: Introductionmentioning
confidence: 99%